2020
DOI: 10.1097/aog.0000000000003869
|View full text |Cite
|
Sign up to set email alerts
|

Elagolix Treatment for Up to 12 Months in Women With Heavy Menstrual Bleeding and Uterine Leiomyomas

Abstract: BR, et al. Elagolix treatment for up to 12 months in women with heavy menstrual bleeding and uterine leiomyomas. Obstet Gynecol 2020;135. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 24 publications
0
66
0
Order By: Relevance
“…With the development of new therapeutic options, including long-term, well-tolerated medical treatments [71][72][73][74][75], the paradigm will potentially change, and give patients the opportunity to use long-term medical therapies indicated specifically for UF. Assessing and communicating the benefits and risks of all choices for women with UF will remain key to ensuring that our patients receive the best available treatment to meet their individual needs.…”
Section: Considerations For Future Management Of Our Patients With Ufmentioning
confidence: 99%
“…With the development of new therapeutic options, including long-term, well-tolerated medical treatments [71][72][73][74][75], the paradigm will potentially change, and give patients the opportunity to use long-term medical therapies indicated specifically for UF. Assessing and communicating the benefits and risks of all choices for women with UF will remain key to ensuring that our patients receive the best available treatment to meet their individual needs.…”
Section: Considerations For Future Management Of Our Patients With Ufmentioning
confidence: 99%
“…GnRH analogs faced the chance of becoming a new trend in this indication, especially after they were introduced into the market in the oral form, for example, elagolix [188] or linzagolix [189]. An increasing number of studies published recently have shown their beneficial influence on UFs and UF-related manifestations [190,191].…”
Section: New Trends and Possible Future Role Of Vitamins In Uterine Fmentioning
confidence: 99%
“…12 The initial trials were extended to 12 months with two groups: elagolix 300 mg twice daily plus low-dose hormone add-back with 1 mg estradiol and 0.5 mg norethindrone acetate once daily (n = 218) or elagolix 300 mg twice daily (elagolix alone) (n = 98). 13 Following 12 months of treatment, heavy menstrual bleeding was controlled in 88% and 89% of women treated with elagolix plus add-back and elagolix alone, respectively. Amenorrhea was reported by 65% of the women in the elagolix plus add-back group.…”
Section: Leuprolide Acetatementioning
confidence: 98%
“…Two women developed liver transaminase levels >3 times the upper limit of normal, resulting in one woman discontinuing treatment. 13 Contraindications to Oriahnn include known allergies to the components of the medication (including the yellow dye tartrazine); high risk of arterial, venous thrombotic or thromboembolic disorders; pregnancy; known osteoporosis; current breast cancer or other hormonally-sensitive malignancies; known liver disease; and concurrent use of organic anion transporting polypeptide 1B1 inhibitors, which includes many HIV antiviral medications. 14 Undiagnosed AUB is a contraindication, and all women prescribed Oriahnn should have endometrial sampling before initiating treatment.…”
Section: Leuprolide Acetatementioning
confidence: 99%